ANALYSIS OF THE VERTICAL SHEAR DESIGN MODEL FOR STEEL‐CONCRETE COMPOSITE SLABS. Issue 4 (27th December 2017) - Pereira, Miguel; Simões, Rui; Duarte, João
Abstract: Usually, the design of composite slabs with short spans, or with current spans with the longitudinal shear behaviour improved by reinforcing systems, is governed by the vertical shear resistance. Nevertheless, the vertical shear resistance of composite slabs, according with european standard EN 1994‐1‐1, is calculated in the same way as reinforcing concrete slabs, being the contribution of the steel sheet not taken into account adequately. In this paper, a reflection and a comparison between vertical shear design models according different standards or methodologies are presented. It is also presented the results of a short experimental programme, composed by 2 experimental tests in composite slabs with short spans, carried out in the Department of Civil Engineering of University of Coimbra.